Ali Mendjeli, a new university town? - CHERRAD , Mohammed Mounir (Journal of Human Sciences, 2020)
The new town Ali Mendjeli results from a voluntarist state policy. It is located in the southern periphery of the Constantine metropolis and has more than 200,000 inhabitants in 2019. Since a decade, this new city is the subject of many studies and debate about its denomination, functions, status and development. From now on, the new city Ali Mendjeli is considered as an autonomous urban entity, economic base, territorial command (wilaya delegated), as well as university pole (2 universities, 3 higher schools) initiated by the State at the time of its creation. In this paper, we will focus our attention on this university function, we suggest that the city does not make the university and that neither the university does, but that they are the product of a double voluntarism, in this case, what would be the territorialization process to achieve for having a university city?